Design multilayer bandpass filter using hairpin resonator for digital broadcasting - Abdullah, Qazwan (2015)
This research presents 2.52-2.65 GHz band-pass filter using multilayer hairpin resonator for digital broadcasting applications . Four-pole resonators are centered at 2.58 GHz with bandwidth of 130 MHz .This filter is simulated using Computer Simulation Technology software (CST) and Advance Design System (ADS) . Filter is designed using Chebychev response with passband ripple of 0. 01 dB . Hairpin-line provides compact structures in the filter design . They can conceptually be obtained by folding the resonators of parallel-coupled half wavelength resonator into a “U” shape . This research will contribute towards a small size filter using the latest multilayer stack up model .The proposed microstrip half wavelength coupled line resonator design is employed to design the multilayer band pass filter . For parallel coupled line band pass filter ,the passband insertion loss using FR4 Material is -5.651dB and when using RO3003 Material is -1.79dB .The passband return loss is -30.614dB for the FR4 material type and -18.52 dB for RO3003 material type. For multi layer band pass filter the passband insertion loss using FR4 Material is -2.23dB and when using RO3003 Material is -1.009dB . The passband return loss is 22.706dB using FR4 material type and -18.99 dB when using RO3003 material type. Filter is fabricated on 1.6 mm thickness FR4 for parallel coupled line with dielectric constant of 4.3.